How much do teachers know about self-regulated learning? To what degree and in what way do they encourage it in students? - Šimić Šašić, Slavica; Nikčević-Milković, Anela; Cindrić, Maja (Frontiers in Education, 2023)
Introduction: Self-regulated learning (SRL) is a multidimensional process that involves personal (cognitive and emotional), behavioural, and contextual components. Teachers, as mediators in socialization, can influence SRL in various direct and indirect ways: by instructing students on effective learning strategies and structuring the learning environment. Most teachers agree that students should be helped to become self-regulated in their learning, however, they are unsure of how to do this, which is why they encourage it to a limited degree. Therefore, the objectives of the research were: 1) to examine how much teachers know about SRL, to what degree and how they encourage it in students; 2) to examine the differences in encouraging SRL with regard to gender, seniority, type of school and status of school subjects they teach.The research was conducted using an online questionnaire at two measurement points. A total of 251/179 primary and secondary school teachers in Croatia participated in the study. To assess teaching knowledge and methods of encouraging SRL, the questionnaire employed both open-ended questions ("Provide your own subjective definition of self-regulated learning."; "How you promote self-regulated learning in your practice? Which approaches are most effective?") and the Self-Regulated Learning (SRL) Encouragement Scale (encouragement of learning planning and learning organization strategies, metacognitive monitoring of learning, elaboration and evaluation, understanding and effort investment).Results: Teachers only partially know what self-regulated learning constitutes. About two-thirds of teachers have heard of the SRL, but only 14% accurately defines the construct. When defining SRL, they most often emphasize independently regulated/directed learning, and the definitions are mostly partially correct. On the other hand, teachers estimate that they encourage SRL to a significant extent. There are certain discrepancies in the data regarding the methods of encouraging SRL depending on the methodology (qualitative/quantitative). Teachers encourage SRL to a limited extent and provide implicit and indirect SRL encouragement. The results indicate that female teachers and teachers in humanities encourage SRL to a greater extent when compared to natural science and technical subject teachers, and the same goes for elective subject teachers when compared to compulsory subject teachers.